2014
DOI: 10.1515/jpm-2014-0069
|View full text |Cite
|
Sign up to set email alerts
|

Pre-pregnancy obesity compromises obstetric and neonatal outcomes

Abstract: Pre-pregnancy obesity is associated with higher incidences of gestational diabetes and preeclampsia. Our study shows that obese women have a higher risk of non-elective cesarean section and preterm birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…Overweight and even more so obesity are major pre-disposing factors for the development of diabetes throughout pregnancy 45 , 46 . Our cohort used for HDL isolation could not be matched for maternal BMI; mothers in the GDM group had significantly higher BMI, both before pregnancy and at time of delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Overweight and even more so obesity are major pre-disposing factors for the development of diabetes throughout pregnancy 45 , 46 . Our cohort used for HDL isolation could not be matched for maternal BMI; mothers in the GDM group had significantly higher BMI, both before pregnancy and at time of delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated that non‐White women were 3 times more likely to develop GDM. Obesity and high BMI have been consistently shown to be associated with an increased risk of GDM (Athukorala, Rumbold, Willson, & Crowther, ; Crane, White, Murphy, Burrage, & Hutchens, ; Hancke et al., ). Likewise in this study, women experienced a 6% increased risk of GDM for every BMI unit increase.…”
Section: Discussionmentioning
confidence: 99%
“…Data from prospective cohort studies showed that normal weight women had a higher significant risk of gaining less weight than what was recommended. 5 Women with lower gestational weight gain had an increased risk for preterm birth, low birth weight, small for gestational age babies and a decreased risk for caesarean birth. 6 A population-based study was done in the United States of America involving 124,348 pregnant women to assess their GWG.…”
Section: How To Cite This Articlementioning
confidence: 99%
“…8 12.5 -18.0 19.8 -26.0 11.5 -16.0 26.1 -29.0 7.0 -11.5 > 29 7 Table 1 As per the BMI categories proposed by WHO, the advised weight gain was as follows 4 Pre-pregnancy BMI Recommended Weight Gain in kgs < 18. 5 12.5 -18.0 18.5 -24. 9 11.5 -16.0 25.0 -29.…”
Section: How To Cite This Articlementioning
confidence: 99%